PkM PELATIHAN PENERAPAN TES KEBUGARAN JASMANI INDONESIA (TKJI) - Haeril Haeril; Muhammad Akbar Syafruddin; Akbar Yusuf; Ariana Asri (Jurnal Pengabdian Olahraga Masyarakat (JPOM), 2022)
This PkM activity was carried out with the aim of providing understanding to students who are members of the UKM Sport YPUP Makassar regarding the implementation of the TKJI test. This PkM is carried out by providing assistance and training to all UKM members regarding the implementation of the TKJI test. The participants in this activity are active members of UKM Sport YPUP Makassar, totaling 32 people. The results of this PkM show that there is an increasing number of UKM members who understand the implementation of the TKJI test. This can be seen from the results of the initial and final tests which have increased by 72.35%.